Stigmergy sebagai Strategi Transformasi Desain Arsitektur Berbasis Waktu - Nabawi, Nur Hadiyatun; Paramita, Kristanti Dewi (Universitas Sebelas Maret Surakarta, 2026)
Stigmergy as a Time-Based Architectural Design Transformation StrategyThis article explains that conventional architecture still tends to see buildings as static objects, so changes after occupation are often treated merely as operational effects rather than as part of design strategy. This view limits the understanding of architecture as a system that continuously develops through interactions among users, materials, activities, and the environment. The study proposes a conceptual model by synthesizing the agent–medium–trace relationship, identifying five stigmergy systems in spatial contexts, and reformulating the link between system mechanisms and phases of temporal transformation. The results reveal four phases of spatial transformation—Activation, Intensification, Structural Shift, and Reconfiguration—which operate through five systems: controlling, guiding, protecting, direction, and zoning. The article’s main contribution is the Strategic Temporal Transformation Matrix, which positions time as a strategic framework for understanding design transformation and supporting adaptive spatial and environmental systems that evolve gradually over time.